2005
DOI: 10.1111/j.1365-2494.2005.00491.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of calcium silicate on growth and dry matter yield of Chloris gayana and Sorghum sudanense under two soil water regimes

Abstract: The effects of five rates [0 (control), 1, 2, 4 and 6 Mg ha )1 ] of calcium silicate on the growth and water consumption by rhodes grass (Chloris gayana Kunth) and sudan grass (Sorghum sudanense Piper) under wet and dry soil water regimes (60 g and 30 g H 2 O kg )1 soil respectively) were evaluated in a pot experiment. The effect of the application of silicate on plant biomass was similar to that of the control. However, the shoot and root dry mass varied significantly (P < 0.001) according to the soil water r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…The alleviating effects of silicon on stresses like diseases, drought, salinity, heavy metals, UV-B radiation, etc. have been intensively studied (Peaslee and Frink 1969;Ma 2004;Eneji et al 2005;Liang et al 2007;Kaya et al 2009;Shen et al 2009Shen et al , 2010a. Aluminium accumulation in the stressed peanut was greatest in the root, and less in the stem and leaf.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The alleviating effects of silicon on stresses like diseases, drought, salinity, heavy metals, UV-B radiation, etc. have been intensively studied (Peaslee and Frink 1969;Ma 2004;Eneji et al 2005;Liang et al 2007;Kaya et al 2009;Shen et al 2009Shen et al , 2010a. Aluminium accumulation in the stressed peanut was greatest in the root, and less in the stem and leaf.…”
Section: Discussionmentioning
confidence: 99%
“…Its beneficial effects on plant growth have been widely evidenced, especially for plants subjected to biotic and abiotic stresses, such as diseases, pests, drought, salinity, cold, heavy metals, UV-B radiation and nutrient imbalance (Epstein 1999;Ma 2004;Eneji et al 2005;Liang et al 2007;Kaya et al 2009;Shen et al 2009Shen et al , 2010a. Silicon-mediated Al toxicity has been reported in several plant species, such as tomato (Peaslee and Frink 1969), sorghum (Hodson and Sangster 1993), barley (Hammond et al 1995), wheat (Cocker et al 1998) and maize (Kidd et al 2001;Wang et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Wheat plants subjected to drought and treated with Si maintained higher stomatal conductance, relative water content, and water potential than non-treated plants. Besides, leaves were larger and thicker, thereby limiting the loss of water through transpiration (Gong et al 2003;Hattori et al 2005) and reducing water consumption (Eneji et al 2005). Along the same line, in the case of rice, Si increased resistance to typhoons (Ma et al 2001b), probably because of the rigidity gained by the silicification of shoots.…”
Section: Other Stressesmentioning
confidence: 98%
“…Indeed, repeated crop exports can reduce the concentration of potentially available Si present as phytoliths to the extent that Si fertilization is necessary (Datnoff and Rodrigues 2005;Eneji et al 2005;Meunier et al 2008;Savant et al 1997a) because a fraction of plant Si does not return to the soil. For example, Desplanques et al (2006) showed that if we consider amorphous silica as the only source of Si for plants, the stock of available Si from a rice field of Camargue (France) would be exhausted after 5 years of cultivation.…”
Section: The Phytolith Poolmentioning
confidence: 99%
“…In plant tissues, Si is always coupled with other elements and immobilized by biomineralization as phytoliths (plant opals) in cell wall, cell lumen and intercellular spaces (Parr & Sullivan, ; Prychid, Rudall, & Gregory, ; Song, Liu, et al., 2012; Song, Wang, et al., 2012) or deposited as a Si double layer beneath the cuticle (Ma & Yamaji, ; Schaller, Brackhage, Bäucker, & Dudel, ; Schaller et al., ). Deposition of Si in plant tissues can improve plant structural integrity (Epstein, ; Hodson, White, Mead, & Broadley, ) and increase plant tolerance to diseases (Cherif & Belanger, ; Kanto, Maekawa, & Aino, ), drought (Eneji et al., ) and metal toxicities (Richmond & Sussman, ; Shi et al., ).…”
Section: Introductionmentioning
confidence: 99%